An Inner and Outer Gate Complex at Tell en-Nasbeh - Zorn, Jeffrey R. (Bulletin of ASOR, 1997)
At Tell en-Nasbeh (Mizpah), W. F. Badè uncovered a two-chamber gate at the northeast corner of the site and a four-chamber gate on the east side. The relationship of these gates to each other, and to the offset-inset wall of King Asa of Judah, has puzzled scholars. Most have assumed that the four-chamber gate was never completed or only functioned as the settlement's gate until an Assyrian destruction in 701 B. C. It is more likely that the two gates are a single, Inner-Outer Gate complex, built by Asa in the ninth century B. C., which functioned until the Babylonian destruction of Jerusalem in 586, after which the four-chamber gate was replaced by new constructions associated with the transformation of Mizpah into an administrative center under Gedaliah. The two-chamber gate functioned until the fifth century B. C. Fresh evaluations of the topography in the intergate area, the site's stratigraphy and in situ ceramic deposits are marshaled to support this theory.